2011
DOI: 10.1186/1742-2094-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation induces glial aromatase expression in the uninjured songbird brain

Abstract: BackgroundEstrogens from peripheral sources as well as central aromatization are neuroprotective in the vertebrate brain. Under normal conditions, aromatase is only expressed in neurons, however following anoxic/ischemic or mechanical brain injury; aromatase is also found in astroglia. This increased glial aromatization and the consequent estrogen synthesis is neuroprotective and may promote neuronal survival and repair. While the effects of estradiol on neuroprotection are well studied, what induces glial aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…The ZF brain produces a dramatic and robust increase in glial cells surrounding the injury site (Duncan et al, ; Saldanha et al, ). These glial cells are capable of altering steroid hormone sensitivity and have shown that steroid hormones are rapidly upregulated following injury and potentially serve to decrease neuronal damage (Duncan and Saldanha, ; Duncan et al, ; Walters et al, ). Although it is hard to directly compare across experimental protocols, treatments, and dependent measures, the data suggest that the steroidal response to injury is robust enough to completely dampen the wave of secondary degeneration that is diagnostic of severe brain trauma in humans and other mammals (Duncan et al, ; Pedersen et al, ; Wynne et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The ZF brain produces a dramatic and robust increase in glial cells surrounding the injury site (Duncan et al, ; Saldanha et al, ). These glial cells are capable of altering steroid hormone sensitivity and have shown that steroid hormones are rapidly upregulated following injury and potentially serve to decrease neuronal damage (Duncan and Saldanha, ; Duncan et al, ; Walters et al, ). Although it is hard to directly compare across experimental protocols, treatments, and dependent measures, the data suggest that the steroidal response to injury is robust enough to completely dampen the wave of secondary degeneration that is diagnostic of severe brain trauma in humans and other mammals (Duncan et al, ; Pedersen et al, ; Wynne et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the neuroprotective role of steroid hormones, Roselli (27) reported that brain aromatase is neuroprotective. Indeed, increased aromatase expression is observed following neural injury and neuroinflammation (28,29). Therefore, transcriptional activation of aromatase might prevent neuronal cell death.…”
Section: Discussionmentioning
confidence: 98%
“…First, following the canonical pathway, increased NFκB signaling results in a further increase in cytokine expression causing secondary damage and additional tissue destruction [11]. Second, a neuroprotective pathway is activated where NFκB signaling increases gliosis which results in an increase in aromatase activity in astrocytes [22, 25, 26, 29, 48] but also increased androgen receptors in microglia [45]. Upregulation of these steroids results in inhibition of neuroinflammation by decreasing COX-2 and PGE 2 action [22] and by decreasing NFκB and IκB expression.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking aromatase and thus estrogen production leads to an exacerbation of the inflammation [22] and injury size [27, 28]. Furthermore, glial aromatase expression is induced via neuroinflammation [25] and we hypothesize that this induction is mediated by TNF-α specifically. These data suggest that estrogens interacting with TNF-α and subsequently NFκB may be a potential target for neuroinflammatory mediation.…”
Section: Introductionmentioning
confidence: 99%